Effectiveness of Combined Resistance Exercise and Tai Chi on Lower Limb Muscle Strength in Older Adults with Diabetes Mellitus - Elisabeth Matrona Sintia Pareira; Lidwina Triastuti Listianingsih; Whisnu Trie Seno Ajie (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes Mellitus (DM) is disease metabolic chronic which causes various complications including decline strength muscle extremities below , which impacts mobility and risk falls in the elderly . Research This aim analyze effectiveness of Resistance Exercise with combination of Tai Chi gymnastics against improvement strength leg muscles in the elderly with DM. Research design use quasi experimental one group pretest –posttest with amount sample of 32 elderly in the Community Seroja Cahya Kawaluyan Hospital . Intervention done for 3 months with frequency 3 times/ week , intensity moderate (50–70%), and duration 45 minutes . Strength muscle legs measured use leg dynamometer . Data not normally distributed (Shapiro-Wilk p < 0.05), so that analysis using the Wilcoxon test. The results showed 26 elderly experience improvement strength muscles , 3 experienced decrease , and 3 remains , with mark Asymp . Sig. 0.000 (< 0.05), so proven there is improvement strength significant leg muscles after intervention . Exercise program This can recommended as intervention safe and effective for elderly with DM for increase strength muscles and function mobility .